Comparative study of the Martian suprathermal electron depletions based on Mars Global Surveyor, Mars Express, and Mars Atmosphere and Volatile EvolutioN mission observations. Issue 1 (9th January 2017) - Steckiewicz, M.; Garnier, P.; André, N.; Mitchell, D. L.; Andersson, L.; Penou, E.; Beth, A.; Fedorov, A.; Sauvaud, J.‐A.; Mazelle, C.; Brain, D. A.; Espley, J. R.; et al.
Abstract: Nightside suprathermal electron depletions have been observed at Mars by three spacecraft to date: Mars Global Surveyor, Mars Express, and the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. This spatial and temporal diversity of measurements allows us to propose here a comprehensive view of the Martian electron depletions through the first multispacecraft study of the phenomenon. We have analyzed data recorded by the three spacecraft from 1999 to 2015 in order to better understand the distribution of the electron depletions and their creation mechanisms. Three simple criteria adapted to each mission have been implemented to identify more than 134, 500 electron depletions observed between 125 and 900 km altitude. The geographical distribution maps of the electron depletions detected by the three spacecraft confirm the strong link existing between electron depletions and crustal magnetic field at altitudes greater than 170 km. At these altitudes, the distribution of electron depletions is strongly different in the two hemispheres, with a far greater chance to observe an electron depletion in the Southern Hemisphere, where the strongest crustal magnetic sources are located. However, the unique MAVEN observations reveal that below a transition region near 160–170 km altitude the distribution of electron depletions is the same in both hemispheres, with no particular dependence on crustal magnetic fields. This result supports the suggestion made by previous studies that these low‐altitudes events are produced through electron absorption by atmospheric CO2 . Key Points: Automatic detection of suprathermal electron depletions observed by three spacecraft (MGS, MEX, and MAVEN) during 17 years At high altitudes electron depletions are clearly observed by the three spacecraft over crustal magnetic field sources At low altitudes interaction with crustal magnetic fields is no longer the dominant creation process for electron depletions